Quality of life outcomes of patients with chronic rhinosinusitis after functional endoscopic sinus surgery, prospective cohort study - Laababsi, Rabii (Ann Med Surg (Lond), 2019)
OBJECTIVES: To compare the outcome of patients with unilateral CRSsNP (U CRSsNP) and bilateral CRSsNP (B CRSsNP) undergoing FESS. Also, we evaluate the impact of SNOT-22 domains to predict their quality of life (QOL) outcomes and compare these factors with those of CRSwNP group, published in previous work. METHODS: A prospective cohort study was performed in the hospital 20 August,66 patients who were presented between January 2016 and December 2017 were diagnosed with CRS according to guideline recommendations, and were beforehand refractory to initial medical therapy and elected to FESS. The Sino Nasal Outcome Test-22 (SNOT-22) was used to evaluate QOL. RESULTS: A higher significant improvement was observed between preoperative and postoperative SNOT-22 scores in U CRSsNP group [37.13 ± 9.307 versus 14.11 ± 8.531] and in B CRSsNP group [41.76 ± 6.949 versus 18.57 ± 8.495]. In the U CRSsNP group, patients having a preoperative SNOT-22 score higher than 20 points attained MCID in 88%. For the other group, patients having preoperative SNOT-22 score superior to 40 points achieved MCID in 66%. A multivariate logistic regression model found preoperative predictors that have impact on QOL outcomes. CONCLUSIONS: Outcomes from this study suggest that patients with U CRSsNP having a preoperative SNOT-22 scores between 10 and 19, and patients with B CRSsNP having a preoperative SNOT-22 scores between 10 and 19 or 20–29 had no chance of achieving an MCID improvement after FESS. Also, preoperative rhinologic symptoms and preoperative psychological dysfunction domains of SNOT-22 are helpful tools to predict improvement after FESS unlike the unilateral character of CRS.